2017
DOI: 10.1016/j.triboint.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interfacial mechanism of ZDDP tribofilm in humid environment and its effect on tribochemical wear; Part I: Experimental

Abstract: Wear performance of any tribological system can be influenced in a complex way by water contamination. Water can be the cause of steel corrosion which, in turn, can accelerate wear. It can decompose the additives in the oil and create a more corrosive environment which leads to the higher wear in the system. A key novelty of this study is to investigate the effect of relative humidity and the tribochemical changes on the tribological performance and tribofilm characteristics of boundary lubricated systems by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
4
18
0
1
Order By: Relevance
“…Thus, Crobu et al [5] found that some depolymerization of zinc metaphosphate and polyphosphate occurred when this was rubbed against a glass sphere, though much less than when rubbed against steel. These changes were ascribed to the action of adventitious water, and recently Parsaeian et al [6] have shown that the deliberate addition of water does reduce the chain length of ZDDP tribofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Crobu et al [5] found that some depolymerization of zinc metaphosphate and polyphosphate occurred when this was rubbed against a glass sphere, though much less than when rubbed against steel. These changes were ascribed to the action of adventitious water, and recently Parsaeian et al [6] have shown that the deliberate addition of water does reduce the chain length of ZDDP tribofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The chain length of phosphates in ZDDP tribofilms can be estimated from the ratio of bonding oxygen, BO (P-O-P), to non-bonding oxygen, NBO (P=O and P-O-M), intensity, the BO/NBO ratio [4][5][6][7]. It should be noted that many studies have shown that the chain length of zinc polyphosphate reduces with rubbing time [3,6,[8][9][10] though a few have proposed precisely the opposite [11,12]. Parsaeian et al's work [3] thus suggests that the strength/durability of ZDDP tribofilm may depend on its phosphate chain length and thus change with rubbing time.…”
Section: Introductionmentioning
confidence: 99%
“…can produce sulfate [10][11][12] or cleave the phosphate chains composing the tribolm. 11,13 Third, probing the contacting surfaces aer the test can conceal the formation and kinetics of any intermediate species during the initial stage of the decomposition reaction. 14 Fourth, during sliding at high temperature and under high contact pressure, triboemission from the substrate, 15 availability of cations, 16 heat and shear 17 make a continuous environment for chemical reactions to evolve, which cannot be captured completely using only ex situ technique.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced chemical analysis of the tribofilms formed in the presence of ethanol has suggested oxidation of sulfur species into sulfites and reduction in the length of the phosphate chains [14]. Water contamination has also been shown to reduce the thickness and change the structure of ZDDP tribofilms, apparently by reducing the length of the polyphosphate chains [15].…”
Section: Introductionmentioning
confidence: 99%